A new proposal for trust management in wireless sensor networks based on validation. (2017) - Rego, Albert; Gkountis, Christos; García, Laura; Lloret, Jaime
Due to their many advantages, WSNs are getting more and more important in the field of monitoring and control systems. Despite their many advantages WSNs have some disadvantages that need to be solved. Trust-based networking can be applied to WSNs in order to get better their performance. In this paper, we proposed a new model for trust management between sensor nodes in a WSN based on false alarms they produced. The existence of validators in the WSN supports the node to determine if the alarm is a false positive. A communication model is proposed and its messages are described. Furthermore, we have performed several tests to validate the benefits of our proposal, measuring the energy consumed by the network and each individual node in the network in five scenarios. They showed us that not trusting all of the nodes in a WSN, can have better results in the total energy consumption of the network. However, having a high number of malicious nodes causes an increment of energy consumption in the rest of the nodes.